Program Campus Ambassador Sebagai Strategi IMC PT Gojek dalam Meningkatkan Brand Awareness di Kalangan Mahasiswa - Fikran H, Moh; Juwita, Rina (Jayapangus Press, 2025)
The rapidly growing digital technology industry is accompanied by increasingly tight competition, thus encouraging companies to implement various innovative strategies to increase brand awareness, especially among the younger generation. This study analyzes how the marketing communication strategy carried out by PT Gojek in increasing the company's brand awareness among students, through its latest program, Gojek Campus Ambassador. This study is based on qualitative methods, using a mixed approach between literature studies, program-related documentation, and interviews with PT Gojek informants and one of the program participants. The results of the study indicate that the implementation of the Integrated Marketing Communication (IMC) strategy in this program has succeeded in significantly increasing the brand awareness of the company PT Gojek among students, as evidenced by the success of PT Gojek in attracting the interest of more than 72,000 students throughout Indonesia to participate in the Gojek Campus Ambassador program. The IMC strategy implemented in the program in this study combines various elements of communication channels, this study shows that the integration of marketing communication strategies through digital media, direct promotions, and student involvement as campus ambassadors contributes effectively to significantly increasing PT Gojek's brand awareness among students. In addition, the results of this study also found that involving the younger generation in marketing strategies can expand the reach of the audience in increasing brand awareness because through the younger generation can easily build emotional closeness that can increase the relevance of brand acceptance in the targeted market segment, namely students. The conclusion of this study can provide an overview to companies in implementing effective marketing strategies to reach the younger generation market, especially among students, through the concept of Integrated Marketing Communication.